Holistic accountability of Malay/Muslim non-profit organisations in Singapore - Siti Hajjar binte Mohamed Idrus (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2017)
Religious Non-Profit Organisations (NPOs) operating under a sanctified sector will no longer suffice as the public and government call for greater accountability. The most common form of accountability mechanism for both profit and non-profit organisations is by means of disclosure of information. Registered NPOs in Singapore are required to submit a mandatory annual financial report in accordance to accounting requirements to regulators. However, just like a profit making organisation, accountability becomes 'upwardly-inclined' and overemphasis on upward accountability to donors and regulators can prove counterproductive of services delivered to the NPOs' beneficiaries. This study aims to examine the extent of holistic accountability present in Malay/Muslim Organisations' (MMOs) reporting through inputs from upward, downward and lateral accountability. Holistic accountability framework based on Ebrahim's (2003) five accountability mechanisms serve as a guide for NPOs in a multi-stakeholder environment. Using samples of MMOs, a mixed-method approach (QUAN-qual) was adopted. Results from the checklist show that five out of 18 MMOs with score of 60% and above display an upwardly-inclined accountability in reporting to stakeholders. Two out of 18 MMOs have scores of 60% and above, inclining towards lateral accountability. In addition, the use of self-regulation accountability mechanism is consistent across the three levels of accountability. After interviewing seven officers from four MMOs however, results reveal that upward accountability did not overshadow downward and lateral accountability. In fact, downward accountability was given importance with all five mechanisms of Ebrahim (2003) being practised however unreported.